Intersite Charge Transfer Enhanced Oxygen Evolution Reactivity on A2IrO3 (A=Li, Na, Cu) Delafossite Electrocatalysts. Issue 5 (1st May 2022) - Zhu, Chuanhui; Cai, Guo-Hong; Yuan, Chongyang; Huang, Bin; Li, Guangqin; Croft, Mark; Greenblatt, Martha; Li, Man-Rong
Abstract : Exploring a simple model system to realize the intrinsic guidelines of activity for oxide electrocatalysts is urgent and important. Here, we introduce delafossite oxides A 2 IrO3 ( A = Li, Na, Cu) as a family of oxygen evolution reaction electrocatalysts in alkaline media. We show that, in Cu2 IrO3, the intrinsic intersite charge transfer between Cu and Ir improves the electrocatalytic activity by simultaneously increasing the conductivity and reducing the Tafel slope down to 51 mV dec −1 with an overpotential η 10 = 361 mV. Through a comparative study, the improved activity of Cu2 IrO3 is attributed to the increase of Ir 5 d projected electronic density of states with extended Ir–O bond length. This study provides insights into advanced catalyst design through tailoring the active site of oxides by the modulation of electronic states in a given structural motif.